ADDRESSING COGNITIVE ISSUES IN LEARNING ENGLISH GRAMMAR: LEARNED SELECTIVE ATTENTION AND CONCEPTUAL TRANSFER - David Wijaya (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Learning grammar is cognitively demanding and thereby presents a number of difficulties to learners. These difficulties include learned attention and first language conceptual transfer phenomena on the part of the learner. The attention that is learned during first language acquisition and prior to learning English as a second language overshadows and blocks the acquisition of focal aspects of the target grammar, such as the simple past -ed and the suffix -s. These issues are compounded by conceptual categories that are structured and formed also during first language acquisition. Second language researchers have proposed form-focused instruction as a way to deal with these issues. However, research shows that the common traditional approach that is used in this type of instruction does not always specifically address the problems mentioned earlier. As a result, EFL learners remain ill-served. This paper discusses the two cognitive issues that arise from first language learning experience, considers the implications for language teaching and examines various pedagogical options that can address the cognitive issues in question. The reactions are expectedly able to direct learners’ attention to the important aspects and minimize the negative transfer. The overarching goal is to help learners in their acquisition of English grammar. In concluding, I recommend incorporating this approach in EFL instruction.